Innovation Of Food Products Based on Local Agricultural Products as A Strategy To Overcome Stunting In Kamal Village: Inovasi Produk Pangan Berbasis Hasil Pertanian Lokal Sebagai Strategi Penanggulangan Stunting di Desa Kamal - Farras, Ananda; Wahyu Wibowo, Haryo; Aulia Putri Ifanda, Syafira; Ayu Wandari, Fiona; Ali Abilawa, Muhammad; Maulana, Nor; Tristan Prana Raya, Guntur; Arifiani, Devita; Fakhri Maulana, Surya; Iffah Nazihah, Annisa’; Abror, Hadziqul (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a serious problem of chronic nutrition faced by children in Kamal Village, which is caused by various factors such as economic conditions and understanding of nutritious food. This study aims to help reduce stunting rates through an innovation program from the Kamal Promahadesa team. The method of implementing this activity consists of several stages, namely literature studies, observations, counseling, and training in making nutritious food by utilizing local agricultural products in the form of corn and cassava. This activity involves strategic partners who are experts in their fields in implementing direct socialization and education to targets regarding the importance of balanced nutrition and effective parenting patterns. The results of the activities achieved show an increase in community understanding of the nutrition needed for toddler growth and development and help reduce stunting rates among toddlers. This program not only provides solutions to the problem of malnutrition, but also contributes to providing innovation in the use of local agricultural products, namely corn and cassava, which are demonstrated through training in processing nutritious food in the form of cassava nuggets and corn milk. This nutritious food processing innovation provides many benefits in adding new knowledge about how to process ingredients around to be healthier and more nutritious and easy to find and process at an affordable cost. This agricultural product processing innovation functions as a functional food that combines nutrients from cassava and corn to support the growth and development of toddlers in an effort to prevent stunting.